(untitled) (Medicina y Seguridad del Trabajo, 2025)
Introduction: Occupational accidents involving electrical contact are a significant cause of morbidity and mortality in industrial settings. This study analyzes their incidence in Peru between 2010 and 2024, assessing risk factors and proposing preventive strategies based on international regulations. Method: A quantitative, non-experimental, correlational study was conducted based on the analysis of 168 statistical bulletins from the Ministry of Labor and Employment Promotion. Shapiro-Wilk normality tests and Spearman correlation analysis were used to assess the relationship between variables such as total workplace accidents, electrical accidents, fatal accidents, and hazardous incidents. Results: A strong correlation was found between total occupational accidents and electrical accidents (r=0.835; p<0.01), and a moderate correlation with total fatal accidents (r=0.601; p<0.05). A significant correlation was also found between hazardous incidents and electrocution deaths (r=0.608; p<0.05), suggesting that near-misses may predict fatal events. However, no significant correlation was found between electrical accidents and hazardous incidents (r=-0.061). Conclusions: Although electrical accidents represent a small percentage of total accidents, their clinical severity and potential lethality require priority attention. It is recommended that the implementation of international standards such as ISO 45001, NFPA 70E, and OSHA be strengthened, prioritizing technical training, the use of personal protective equipment, and proactive monitoring systems. The findings support the development of more effective public policies for the prevention of electrical hazards in high-exposure sectors.